Can we turn the tide? Confronting gender inequality in climate policy - Huyer, Sophia; Acosta, Mariola; Gumucio, Tatiana; Ilham, Jasmin Irisha Jim (Informa UK Limited, 2020)
Emerging global crises such as climate change, massive migrations, pandemics, and environmental degradation are posing serious risks to humanity, threatening ecosystems and rural livelihoods across the globe. The poor, and especially the most marginalised among the poor, are disproportionately affected. Climate change in particular is expected to exacerbate pre-existing social inequalities, including gender inequalities. Therefore, innovative and equitable climate adaptation and mitigation strategies will be needed. This article reviews the progress so far in integrating a gender perspective into climate change policy discussions and agreements at global and national levels.